Memorandum of understanding between Universiti Teknologi MARA and Al Jazeera Media Network / Fakulti Komunikasi dan Pengajian Media - Universiti Teknologi MARA, Fakulti Komunikasi dan Pengajian Media (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding for students' internship placement, training programs and collaborations and appointment of adjunct scholar.